The Influence of Constructivist Pedagogy Training Programs on ECCE Teachers' Professional Competence in Designing Child-Centered Learning - Salamah, Mar’atus (Generasi, 2025)
Backround: Early childhood education increasingly emphasizes child-centered pedagogical approaches rooted in constructivist theory, yet many teachers struggle to translate these principles into effective classroom practice. The gap between theoretical understanding and practical implementation highlights the critical need for comprehensive professional development programs that enhance teachers' competence in designing authentic child-centered learning experiences.Objective: This study examines the influence of constructivist pedagogy training programs on early childhood teachers' professional competence in designing child-centered learning, exploring transformations in pedagogical knowledge, curriculum planning abilities, learning environment design skills, and classroom practice implementation.Method: A qualitative phenomenological approach was employed with fourteen (N=14) ECCE teachers participating in a structured constructivist pedagogy training program. Data collection included in-depth interviews, focus group discussions, classroom observations, pedagogical documentation analysis, and reflective journals.Findings and Implications: Thematic analysis identified patterns in teachers’ competence development and implementation experiences. Teachers demonstrated substantial improvements in pedagogical knowledge, planning competencies, and child-centered practice implementation. Professional identity transformation emerged as foundational to sustained practice change. However, contextual factors including institutional pressures, resource limitations, and administrative support significantly influenced implementation quality.Conclusion: Findings suggest that effective professional development requires sustained engagement, practice-based learning, attention to professional identity, and systemic approaches addressing enabling conditions beyond individual teacher competence. Well-designed constructivist pedagogy training substantially enhances teachers' professional competence in child-centered learning design, though successful implementation requires supportive contextual conditions alongside individual competence development.